Latvijas komercbanku pasīvu analīze - Kolodjažnaja, Aļona (Latvijas Universitāte, 2019)
Bakalaura darba tēma ir „Latvijas komercbanku pasīvu analīze”. Darba mērķis ir veikt Latvijas komercbanku pasīvu analīzi - īpašu uzmanību pievēršot noguldījumiem. Atbilstoši izvirzītajam darba mērķim tika definēti Bakalaura darba galvenie uzdevumi: 1.Veikt dokumentu, likumu un normatīvo aktu izpēti, kas raksturo un nosaka Latvijas banku sektoru darbību; 2.Raksturot komercbanku pasīvus; 3.Veikt Latvijas komercbanku pasīvu analīzi; 4.Sniegt secinājumus par pašreizējo stāvokli un izstrādāt priekšlikumus komercbanku pasīvu pilnveidošanai un darbības efektivitātes uzlabošanai. Pēc iegūtajiem rezultātiem izstrādāti secinājumi un sniegti priekšlikumi Latvijas komercbanku efektīvākai pasīvu pārvaldīšanai. Bakalura darba apjoms ir 63 lpp. Darbs sastāv no 3 nod., 28 att., 2 tab., 35 literatūras avotiem un 5 pielikumi. Atslēgvārdi: pasīvi, komercbanku resursi, noguldījumi, pasīvu analīze

The theme of this bachelor’s thesis is “ Analysis of Latvian commercial banks liabilities”. The aim of the thesis is to carry out the analysis of Latvian commercial banks liabilities - paying more attention to depositing. According to the main goals, the main set tasks of the Bachelor thesis where: 1. To carry out research of documents, laws and normative acts that characterize and determine the activity of Latvian banking sectors; 2. To characterize the liabilities of the commercial banks. 3. To carry out analysis of Latvian commercial banks liabilities; 4. To provide conclusions on the current situation and develop proposals for the improvement of commercial bank liabilities and improve operational efficiency. Based on the results obtained, conclusions have been developed and proposals for more efficient management of liabilities of Latvian commercial banks have been provided. The length of the thesis is 63 pages. It consists of three parts, 28 illustrations, two tables and five annexes. 35 literature sources have been used. Keywords: Liabilities, Resources of commercial banks, Deposits, Liabilities analysis.
Analysis of Latvian commercial banks liabilities
Keywords: Ekonomika; Liabilities; Resources of commercial banks; Deposits; Liabilities analysis